Recognition, Tolerance and Interculturality. A pending affair in a world of moral strangers - Villarroel, Raúl (Acta Bioethica, 2017)
The complexities of a current interest phenomenon such the unavoidable and increasing situation of coexistence between moral strangers, understood as a fact triggered by the collapse of historical territorial restrictions imposed to the life of people inside national limits, is examined in this paper. Many of these individuals are now forced to migrate and coexist in new geographical spaces, where they must face their differences, without the social skills that would allow them to interact by coordinating action plans, regardless of conflicting dimensions, or freed from xenophobic prejudice and intolerance. This paper seeks to find an empirical correlate to this argument and meditate about the problems of recognition, tolerance and interculturality in a social scene, close to our own national experience. The subject of recognition is referred to those deep cultural differences that could emerge between individuals who are compelled to share a new vital and biographical space. This will be analyzed in correspondence to the problems arising from the demands of recognition raised today by the Mapuche people to the chilean State.